Antidiabetic and antimicrobial activities of fractions and compounds isolated from Berberis brevissima Jafri and Berberis parkeriana Schneid (Bangladesh Journal of Pharmacology, 2013)
Methanol extracts of the roots of B. brevissima and B. parkeriana were examined for antidiabetic and antimicrobial activities. Six compounds i.e berberine, 8-oxo-berberine, dehydrocheilanthifoline, columbamine, jatrorrhizine and gluta-mic acid were isolated from the active fractions of these species for the first time. The antidiabetic activity was determined against Protein Tyrosine Phosphatase 1B (PTP 1B), a negative insulin regulator while the antimicrobial activity was performed against four bacterial strains: Mycobacterium marinum ATCC BAA535, sporadic Methicillin Resistant Staphylococcus aureus (SMRSA), endemic Methicillin Resistant Staphylococcus aureus (EMRSA) and Escherichia coli ATCC.8739 at different concentrations.  Amongst the isolated compounds 8-oxo-berberine was found to be the most active antidiabetic (29 % of the positive control) while jatrorrhizine was the most active and selective antimicrobial against SMRSA and EMRSA (-1.2% of the DMSO (D) control).